Defects in IL-2R Signaling Contribute to Diminished Maintenance of FOXP3 Expression in CD4(+)CD25(+) Regulatory T-Cells of Type 1 Diabetic Subjects - Long, S. Alice (American Diabetes Association, 2010)
OBJECTIVE: In humans, multiple genes in the interleukin (IL)-2/IL-2 receptor (IL-2R) pathway are associated with type 1 diabetes. However, no link between IL-2 responsiveness and CD4(+)CD25(+)FOXP3(+) regulatory T-cells (Tregs) has been demonstrated in type 1 diabetic subjects despite the role of these IL-2–dependent cells in controlling autoimmunity. Here, we address whether altered IL-2 responsiveness impacts persistence of FOXP3 expression in Tregs of type 1 diabetic subjects. RESEARCH DESIGN AND METHODS: Persistence of Tregs was assessed by culturing sorted CD4(+)CD25(hi) natural Tregs with IL-2 and measuring FOXP3 expression over time by flow cytometry for control and type 1 diabetic populations. The effects of IL-2 on FOXP3 induction were assessed 48 h after activation of CD4(+)CD25(−) T-cells with anti-CD3 antibody. Cytokine receptor expression and signaling upon exposure to IL-2, IL-7, and IL-15 were determined by flow cytometry and Western blot analysis. RESULTS: Maintenance of FOXP3 expression in CD4(+)CD25(+) Tregs of type 1 diabetic subjects was diminished in the presence of IL-2, but not IL-7. Impaired responsiveness was not linked to altered expression of the IL-2R complex. Instead, IL-2R signaling was reduced in Tregs and total CD4(+) T-cells of type 1 diabetic subjects. In some individuals, decreased signal transducer and activator of transcription 5 phosphorylation correlated with significantly higher expression of protein tyrosine phosphatase N2, a negative regulator of IL-2R signaling. CONCLUSIONS: Aberrant IL-2R signaling in CD4(+) T-cells of type 1 diabetic subjects contributes to decreased persistence of FOXP3 expression that may impact establishment of tolerance. These findings suggest novel targets for treatment of type 1 diabetes within the IL-2R pathway and suggest that an altered IL-2R signaling signature may be a biomarker for type 1 diabetes.